2017
DOI: 10.1002/anie.201608873
|View full text |Cite
|
Sign up to set email alerts
|

Block Copolymer Micellization as a Protection Strategy for DNA Origami

Abstract: DNA nanotechnology enables the synthesis of nanometer-sized objects that can be site-specifically functionalized with a large variety of materials. For these reasons, DNA-based devices such as DNA origami are being considered for applications in molecular biology and nanomedicine. However, many DNA structures need a higher ionic strength than that of common cell culture buffers or bodily fluids to maintain their integrity and can be degraded quickly by nucleases. To overcome these deficiencies, we coated sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
163
1
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(171 citation statements)
references
References 58 publications
0
163
1
7
Order By: Relevance
“…[8][9][10][11] This is due to two main factors involved in degradation of DNA nanostructures upon exposure to biological conditions: i) denaturation caused by low divalent cation concentration (physiological salt concentration approximately 0.04-0.8 mm MgCl 2 ), and ii) digestion caused by the presence of nucleases. [8] Multiple strategies have been developed to chemically or physically prevent the DNA nanostructures from falling apart in cellular media (for example, 10 % FBS), [12][13][14][15][16][17][18][19][20] and in general, encapsulation of DNA nanostructures with different coating moieties prolongs the survival time the longest published. [12,14,[17][18][19] For example, while most bare DNA origami falls apart easily under physiological conditions, PEG-oligolysines, [12] lipid molecules, [17] or cationic polymers [18,19] can be applied as a coating material to extend the half-life of DNA origami by an order of up to approximately 100.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[8][9][10][11] This is due to two main factors involved in degradation of DNA nanostructures upon exposure to biological conditions: i) denaturation caused by low divalent cation concentration (physiological salt concentration approximately 0.04-0.8 mm MgCl 2 ), and ii) digestion caused by the presence of nucleases. [8] Multiple strategies have been developed to chemically or physically prevent the DNA nanostructures from falling apart in cellular media (for example, 10 % FBS), [12][13][14][15][16][17][18][19][20] and in general, encapsulation of DNA nanostructures with different coating moieties prolongs the survival time the longest published. [12,14,[17][18][19] For example, while most bare DNA origami falls apart easily under physiological conditions, PEG-oligolysines, [12] lipid molecules, [17] or cationic polymers [18,19] can be applied as a coating material to extend the half-life of DNA origami by an order of up to approximately 100.…”
mentioning
confidence: 99%
“…[8] Multiple strategies have been developed to chemically or physically prevent the DNA nanostructures from falling apart in cellular media (for example, 10 % FBS), [12][13][14][15][16][17][18][19][20] and in general, encapsulation of DNA nanostructures with different coating moieties prolongs the survival time the longest published. [12,14,[17][18][19] For example, while most bare DNA origami falls apart easily under physiological conditions, PEG-oligolysines, [12] lipid molecules, [17] or cationic polymers [18,19] can be applied as a coating material to extend the half-life of DNA origami by an order of up to approximately 100. [12] Such an encasing strategy, however, often covers the entire outer surface of DNA origami and therefore in theory, makes it difficult to access the DNA strands post-coating.…”
mentioning
confidence: 99%
“…DNA origami nanostructures were preferentially accumulated in the kidneys of mice, and were therapeutically efficacious in mice with acute kidney injury. Electrostatic association of a block co‐polymer, PEG‐PLys (poly(ethylene glycol)‐ b‐ poly( l ‐Lysine)), with the negatively charged DNA origamis such as flat rectangle (RO), 24‐helix bundle (24‐HB), 6‐helix bundle (6‐HB), and wireframe dodecahedron (D‐truss) form polyplex micelles . The DNA origami polyplex micelles (DOPMs) are stable and functional for at least 16 h in DNase I, or RPMI–10%FBS at 37 °C as well as in a buffer containing no Mg 2+ but 30 × 10 −3 m NaCl.…”
Section: Dna Nanostructure Stability and Biocompatibilitymentioning
confidence: 99%
“…To protect DNA origami against high ionic strength (30 m m Na + ) and complex cell culture environment (10 % FBS), Schmidt's group demonstrated an approach by coating the DNA nanostructures with cationic poly(ethylene glycol)‐polylysine (PEG‐PLys) block copolymers, which electrostatically covered the DNA nanostructures to form DNA origami polyplex micelles. By optimizing the length of copolymer, the PEG‐PLys coating strategies were also compatible for oligonucleotide‐stabilized AuNPs or streptavidin‐coated Qdots assembly on the origami template via DNA hybridization or protein‐ligand interactions . Shih's group demonstrated that DNA nanostructures coated by oligolysines with appropriate ratio of nitrogen in lysine to phosphorus in DNA, were stable in low salt conditions.…”
Section: The Issues Of Dna Nanostructures For Drug Deliverymentioning
confidence: 99%
“…sembly on the origami template via DNA hybridization or protein-ligand interactions. [65] Shih's group demonstrated that DNA nanostructures coated by oligolysines with appropriate ratio of nitrogen in lysine to phosphorus in DNA, were stable in low salt conditions. Oligolysine-PEG-stabilized strategies showede nhanced protection against digestion by serum nucleasesa nd more resistant to DNase Id igestion than uncoated structures.…”
Section: Stability Of Dna Nanostructuresmentioning
confidence: 99%